Perencanaan Pengembangan Desa Digital di Kauditan I - Pangemanan, Anando Archie Alexander; Karouw, Stanley David Sualang; Rindengan, Yaulie Deo Y (Jurnal Teknik Informatika, 2021)
Abstract — The digital village is a program that implements a government service system concept, community service, and community empowerment based on the use of information technology. In a digital village, public services will be digital by being connected via a wireless network. Digital services will encourage the improvement of public services in villages and make it easier for village governments to evaluate and improve services with databases that will later be owned. The purpose of this research is to develop an android-based mobile correspondence application. This research uses the Prototype model method with the development process covering several stages. the stages for a prototyping are identifying user needs, developing a prototype, determining whether the prototype is acceptable, using the prototype. The final result obtained from this research is in the form of a product, namely an android mobile application for making correspondence for the Kauditan I community. The letter development application has been created by connecting the Kauditan I Digital Village website with an android application using the android webview system.Key words—Android; Digital; Mobile; Village; Website;